The Principle of Non-Discrimination in Fulfilling the Voting Rights of Disabled Groups in General Elections - Asep Sapsudin (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
This study aims to analyze the legal guarantees of the principle of non-discrimination in fulfilling the voting rights of people with disabilities in general elections in Indonesia and to identify technical obstacles to its implementation in practice. The right to vote is a constitutional right of citizens that must be fulfilled without exception. This study uses a normative legal research method with a statute approach and a conceptual approach. Secondary data sourced from primary, secondary, and tertiary legal materials were analyzed qualitatively and descriptively. The results show that normatively, Indonesia has a strong and multi-layered legal framework, starting from the 1945 Constitution, the ratification of the Convention on the Rights of Persons with Disabilities (CRPD), and the Election Law, that mandates affirmative policies for people with disabilities. However, empirically, technical implementation at polling stations (TPS) still faces serious obstacles. These barriers include limited physical accessibility for wheelchair users, limited voting aids (braille templates), the lack of visual communication media for deaf voters, inaccurate data on the Permanent Voter List (DPT), and low sensitivity among polling station (KPPS) officers. The conclusion of this study emphasizes the need for standardization and audits of polling station (TPS) accessibility, reform of the technical guidance curriculum for election organizers through disability awareness training, and strengthening synergy with organizations for people with disabilities to achieve inclusive and equitable elections.